PERSEPSI SISWA TERHADAP KEGIATAN PRAKTIKUM BIOLOGI DI SMA NEGERI PEKANBARU - Irma S Gultom Irma S Gultom; Arnentis '; Yuslim Fauziah Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the perceptions of students about the activity of biology practical work in Senior High School (SMA) Negeri Pekanbaru. The research was conducted in SMA Negeri who implement biology practical work at Pekanbaru city lesson years 2013/2014 in January-June 2014. Kind of this research was descriptive research. Population were all students in SMA Negeri Pekanbaru. The technique used purposive sampling, was students school grade XI IPA who already implement biology practical work, amounted to 330 people from 13 school,were: SMAN1, SMA3, SMAN4, SMAN5, SMAN6, SMAN7, SMAN8, SMAN9, SMAN10, SMAN11, SMAN12, SMAN13, SMAN14 The technique data collecting used closed questionnaire for students school grade XI IPA and open questionnaire or interview for biology teachers school grade X and XI. The data of closed questionnaire analyzed by descriptive statistics and open questionnaire used for addition data for description the perceptions of students about the activity of biology practical work. The activity of practical work contains 4 indicator such as: design, implementation, evaluation, and advanced stage. The results showed that the perceptions of students about the activity of biology practical work with the details of each indicator, such as: design was good (2.81), implementation was good (2.79), evaluation was enough (2.45), and advanced stage was enough (2.42). The factors affecting determine the activity of biology practical work in Senior High School (SMA) Negeri Pekanbaru such as: implementation time, laboratory assistant, completeness equipment and material practical work, teacher’s ability and understanding, student’s quantity, student’s intelligence, and existence biology’s laboratory. Based on this, it can be conclution that the perceptions of students about the activity of biology practical work in Senior High School (SMA) Negeri Pekanbaru determine enough category with average score 2.62.Key words: descriptive research, the activity of biology practical work, students school grade XI IPA